2021
DOI: 10.20429/tag.2021.080101
|View full text |Cite
|
Sign up to set email alerts
|

The Integer-antimagic Spectra of Graphs with a Chord

Abstract: Let A be a nontrival abelian group. A connected simple graph G = (V, E) is Aantimagic if there exists an edge labeling f : E(G) → A \ {0} such that the induced vertex labeling f + : V (G) → A, defined by f + (v) = uv∈E(G) f (uv), is injective. The integer-antimagic spectrum of a graph G is the set IAM(G) = {k | G is Z k-antimagic and k ≥ 2}. In this paper, we determine the integer-antimagic spectra for cycles with a chord, paths with a chord, and wheels with a chord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Conjecture 1 was shown to be true for all of the classes of graphs which were analyzed in [1,4,5,7,8,9]. The purpose of this paper is to provide additional evidence for Conjecture 1 by verifying it for a large family of graphs including all Hamiltonian graphs.…”
Section: Conjecture 1 ([5]mentioning
confidence: 86%
See 2 more Smart Citations
“…Conjecture 1 was shown to be true for all of the classes of graphs which were analyzed in [1,4,5,7,8,9]. The purpose of this paper is to provide additional evidence for Conjecture 1 by verifying it for a large family of graphs including all Hamiltonian graphs.…”
Section: Conjecture 1 ([5]mentioning
confidence: 86%
“…We call the shorter of the two cycles the minor subcycle of C m (l), denoted by C − m (l), and the longer of the two cycles the major subcycle of C m (l), denoted by C + m (l). In [4], the integer-antimagic spectrum for cycles with a chord was determined completely. In Lemma 2.1, it was shown that Z k -antimagicness can be preserved when an edge is added, provided that edge lies on an even cycle.…”
Section: Chorded Cyclesmentioning
confidence: 99%
See 1 more Smart Citation